Colorado State record hailstone near Bethune - Schumacher, Russ, author (Colorado State University. Libraries, 2019)
Full report compiled by Russ Schumacher for a new state record hailstone from August 13, 2019.--taken from website.
State Climate Extremes Committee memorandum.
Keywords: Hail -- Colorado; Precipitation anomalies -- Colorado